2022
DOI: 10.1172/jci.insight.154573
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial glycocalyx degradation mediates surfactant dysfunction and contributes to acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a common cause of respiratory failure yet has few pharmacologic therapies, reflecting the mechanistic heterogeneity of lung injury. We hypothesized that damage to the alveolar epithelial glycocalyx, a layer of glycosaminoglycans interposed between the epithelium and surfactant, contributes to lung injury in patients with ARDS. Using mass spectrometry of airspace fluid noninvasively collected from mechanically ventilated patients, we found that airspace glycosaminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
(85 reference statements)
1
28
0
Order By: Relevance
“…After exposure to an infectious pathogen or inflammatory insult, alteration in the composition of the GL is one of the earliest features during sepsis [ 65 , 68 ]. Following infection, acute injury, or inflammatory conditions, glucuronidases, such as heparanases (HPSEs) [ 58 , 66 , 79 ], reactive oxygen species (ROS) [ 65 ], and other proteases [ 5 , 80 , 81 ], cause shedding of HS and PGs [ 25 , 57 , 82 ]. Subsequently, adhesion molecules such as E-selectin and intercellular adhesion molecules are exposed on the denuded endothelium [ 6 , 40 , 80 , 83 ], which result in accelerated inflammation [ 84 ], vascular permeability [ 58 , 85 ], oedema, platelet aggregation, hypercoagulation, and a loss of vascular responsiveness [ 3 , 40 , 65 , 68 , 86 , 87 ].…”
Section: Sepsis Model Degradation Of the Glycocalyxmentioning
confidence: 99%
See 1 more Smart Citation
“…After exposure to an infectious pathogen or inflammatory insult, alteration in the composition of the GL is one of the earliest features during sepsis [ 65 , 68 ]. Following infection, acute injury, or inflammatory conditions, glucuronidases, such as heparanases (HPSEs) [ 58 , 66 , 79 ], reactive oxygen species (ROS) [ 65 ], and other proteases [ 5 , 80 , 81 ], cause shedding of HS and PGs [ 25 , 57 , 82 ]. Subsequently, adhesion molecules such as E-selectin and intercellular adhesion molecules are exposed on the denuded endothelium [ 6 , 40 , 80 , 83 ], which result in accelerated inflammation [ 84 ], vascular permeability [ 58 , 85 ], oedema, platelet aggregation, hypercoagulation, and a loss of vascular responsiveness [ 3 , 40 , 65 , 68 , 86 , 87 ].…”
Section: Sepsis Model Degradation Of the Glycocalyxmentioning
confidence: 99%
“…It contributes to neutrophil adhesion, leading to diffuse alveolar damage, interstitial lung oedema, and clot formation during acute lung injury in sepsis and ARDS [ 61 , 68 , 78 ]. There exists a clear association between alveolar epithelial and endothelial GL shedding and the establishment of ARDS [ 81 , 82 ] and COVID-19 [ 4 ]. Moreover, circulating HS fragments are capable of influencing growth factors and other signaling pathways distant to the site of GL injury, which explains the systemic (i.e.…”
Section: Sepsis Model Degradation Of the Glycocalyxmentioning
confidence: 99%
“…More specifically, we found that plasma levels of markers of endothelial glycocalyx degradation (syndecan and heparan sulfate fragments), heparan sulfate proteoglycan cleaving enzymes (heparanase and MMP2), and endothelial activation (vWF and thrombomodulin) are elevated in MCD. Rizzo et al also demonstrated that glycocalyx degradation in the lung is associated with Article surfactant release to the circulation (Rizzo et al, 2022). Based on these observations, endothelial dysfunction in MCD could act as a mechanism favoring the release to the circulation of surfactants from active respiratory tract infections as well as facilitate the interaction of high molecular weight surfactants with podocyte SIRPa.…”
Section: Limitations Of the Studymentioning
confidence: 95%
“…Recent data reveal important roles for the alveolar epithelial glycocalyx in lung injury pathogenesis. The glycocalyx regulates cellular barrier function and cell adhesion (reviewed in [ 10 ]), and glycocalyx shedding can mediate lung disease [ 70 , 71 , 72 , 73 ]. In patients with ARDS, glycosaminoglycan accumulation in respiratory specimens, likely a marker of glycocalyx proteoglycan shedding, correlates with alveolar barrier permeability indices, duration of mechanical ventilation, and matrix metalloproteinase 7 (MMP-7) levels [ 72 , 73 ].…”
Section: Alveolar Epithelial Responses That Lead To Lung Injurymentioning
confidence: 99%
“…The glycocalyx regulates cellular barrier function and cell adhesion (reviewed in [ 10 ]), and glycocalyx shedding can mediate lung disease [ 70 , 71 , 72 , 73 ]. In patients with ARDS, glycosaminoglycan accumulation in respiratory specimens, likely a marker of glycocalyx proteoglycan shedding, correlates with alveolar barrier permeability indices, duration of mechanical ventilation, and matrix metalloproteinase 7 (MMP-7) levels [ 72 , 73 ]. MMP-7, via shedding of syndecan-1, a proteoglycan prominently expressed by the lung epithelium, promotes alveolar airspace neutrophil recruitment and activation after various injuries [ 74 , 75 ].…”
Section: Alveolar Epithelial Responses That Lead To Lung Injurymentioning
confidence: 99%